2015
DOI: 10.3892/or.2015.4232
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-α/β enhances temozolomide activity against MGMT-positive glioma stem-like cells

Abstract: Glioma is one of the most common primary tumors of the central nervous system in adults. Glioblastoma (GBM) is the most lethal type of glioma, whose 5-year survival is 9.8% at best. Glioma stem-like cells (GSCs) play an important role in recurrence and treatment resistance. MGMT is a DNA repair protein that removes DNA adducts and therefore attenuates treatment efficiency. It has been reported that interferon-α/β (IFN-α/β) downregulates the level of MGMT and sensitizes glioma cells to temozolomide. In the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 29 publications
4
16
0
Order By: Relevance
“…In addition, a clinical trial demonstrated that combination treatment involving TMZ and the cytokines IFN-α/β did not significantly improve the overall prognosis of glioma patients. 37 In the present study, after poly(I:C) was delivered to the brain by the IN route, IFN-I production peaked on day 13 and remained at a high level until day 21 ( Figure 4B-D), and anti-tumor immunity was ultimately activated. This finding implies that continuous cancer cell-autonomous IFN-I signaling is required for ICD.…”
supporting
confidence: 49%
“…In addition, a clinical trial demonstrated that combination treatment involving TMZ and the cytokines IFN-α/β did not significantly improve the overall prognosis of glioma patients. 37 In the present study, after poly(I:C) was delivered to the brain by the IN route, IFN-I production peaked on day 13 and remained at a high level until day 21 ( Figure 4B-D), and anti-tumor immunity was ultimately activated. This finding implies that continuous cancer cell-autonomous IFN-I signaling is required for ICD.…”
supporting
confidence: 49%
“…IHC staining was performed as reported previously 35 . The expression level of TNC in glioma tissues was scored as the proportion of the area with positive staining (0-100%) multiplied by the staining intensity (0, negative; 1, weak; 2, moderate; 3, intense).…”
Section: Immunohistochemical (Ihc) Stainingmentioning
confidence: 99%
“…The role of TNC in glioma cell proliferation was evaluated via cell growth assays, as reported previously 35 . Briefly, 5000 cells were seeded in each well in 6-well plates.…”
Section: Proliferation Assaymentioning
confidence: 99%
“…Multiple studies, including our own, have evaluated the combination of IFN-β with Temozolomide (TMZ), the standard-of-care chemotherapeutic for GBM patients 42 (on mature GBM cells and Glioma stem cells both in culture and in vivo 41,4347 ). Such combination therapy was also evaluated on GBM patients 48, 49 .…”
Section: Discussionmentioning
confidence: 99%